Deconstructivist architects (New York, NY. : Michael Blackwood Productions, 2006)
Interviews with architects currently designing deconstructivist architectural projects, a new international design movement that is now challenging post-modernism and transforming modernism. Both young and established architects from Tokyo to London to Los Angeles are developing intense and purposefully 'accidental' works that are not about beautiful composition, symmetry or regular rhythmic order, but about the erosion of what might be called architectural certainty